A Method of Simulated Moments for Estimation of Discrete Response Models Without Numerical Integration - McFadden, Daniel (Econometrica, 1989)
This paper proposes a simple modification of a conventional method of moments estimator for a discrete response model, replacing response probabilities that require numerical integration with estimators obtained by Monte Carlo simulation.This method of simulated moments (MSM) does not require precise estimates of these probabilities for consistency and asymptotic normality, relying instead on the law of large numbers operating across observations to control simulation error, and hence can use simulations of practical size.The method is useful for models such as high-dimensional multinomial probit (MNP), where computation has restricted applications.